FRACTION CIPHER: A WAY TO ENHANCE STUDENT ABILITY IN ADDITION AND SUBTRACTION FRACTION - Mohd Afifi Bahurudin Setambah; Anis Norma Jaafar; Mohammad Ikhwan Mat Saad; Mohd Faiz Mohd Yaakob (Jurnal Infinity, 2021)
Learning the concept of fractions can be one of the most difficult skills to master for primary school students. Fractions are also seen to affect other mathematical knowledge, such as algebra. Researchers have introduced an innovation called Fraction Cipher to help students learn fractions. Fraction Cipher is an innovation in the arena of education that involves learning the Malay language and Mathematics. Design research is used as the research method to solve this problem consisting of three phases: preliminary design, teaching experiment, and retrospective analysis. The instruments used are fraction cipher, fraction test, and observation checklist. The results of the pair's comparative study by controlling the type I error using the Bonferroni method show that the mean values of the mathematical achievement of the experimental group and the control group are significantly different. The results show that Fraction Cipher impacts students to understand and master the concept of fractional addition and fraction subtraction operations. This research also explains the "Sake-Beda" strategy to make it easier for students to solve fractional operation problems. Besides, this study also shows the change in students' attitudes from negative to more positive. Thus, students understand and are more motivated to learn the concept of fractions.